Financial Inclusion and Welfare: Comparison between Male-Headed and Female-Headed Households - Lita Jowanti; Budiono; Anhar Fauzan Priyono (Universitas Udayana, 2025)
Indonesia's Vision 2045 aims to become a high-income country by boosting per capita income and ensuring inclusivity. Financial inclusion is a key national strategy to drive economic growth and equitable welfare. This study examines the effect of household characteristics on financial inclusion and its impact on the welfare of male-headed and female-headed households, using SUSENAS data. Logistic regression and Propensity Score Matching methods were used. The findings reveal that productive mobile phone ownership, non-food expenditure proportion, higher education, productive-age members, social assistance, microenterprises, and urban residence increase the probability of financial inclusion, while agricultural sectors and older household heads reduce it. Financial inclusion positively affects welfare, with greater benefits observed among female-headed households. This study gives policymakers insights into designing more effective financial inclusion strategies to enhance household welfare. Keywords: financial inclusion, gender, propensity score matching, household JEL Classification: G21, J16, C21, D14